PRogram In Support of Moms (PRISM): a pilot group randomized controlled trial of two approaches to improving depression among perinatal women - Nancy Byatt; Tiffany A. Moore Simas; Kathleen Biebel; Padma Sankaran; Lori Pbert; Linda Weinreb; Douglas Ziedonis; Jeroan Allison (Taylor & Francis Group, 2018)
Purpose: This pilot study was designed to inform a larger effectiveness trial by: (1) assessing the feasibility of the PRogram In Support of Moms (PRISM) and our study procedures; and, (2) determining the extent to which PRISM as compared to an active comparison group, the Massachusetts Child Access Psychiatry Program (MCPAP) for Moms alone, improves depression among perinatal women. Methods: Four practices were randomized to either PRISM or MCPAP for Moms alone, a state-wide telephonic perinatal psychiatry program. PRISM includes MCPAP for Moms plus implementation assistance with local champions, training, and implementation of office prompts and procedures to enhance depression screening, assessment and treatment. Patients with Edinburgh Postnatal Depression Scales (EPDS) ≥ 10 were recruited during pregnancy, and completed the EPDS and a structured interview at baseline and 3-12 weeks' postpartum. Results: Among MCPAP for Moms alone practices, patients' (n = 9) EPDS scores improved from 15.22 to 10.11 (p = 0.010), whereas in PRISM practices patients' (n = 21) EPDS scores improved from 13.57 to 6.19 (p = 0.001); the between groups difference-of-differences was 2.27 (p = 0.341). Conclusions: PRISM was beneficial for patients, clinicians, and support staff. Both PRISM and MCPAP for Moms alone improve depression symptom severity and the percentage of women with an EPDS >10. The improvement difference between groups was not statistically significant due to limited power associated with small sample size.